2011
DOI: 10.1021/pr101243j
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of ATM Mediated Gene and Protein Expression Impacting Cellular Metabolism

Abstract: A major goal of systems biology is to decipher cellular responses to genetic perturbations or environmental changes. Network integration of high-throughput data sets such as transcriptomics, proteomics, and metabolomics ("3-omics") offers a powerful tool for understanding the regulation and organization of cellular functions and biological processes. Given that the ATM (the product of the ataxia-telangiectasia mutated) gene exhibits multifaceted functions involved in complex biological networks, we attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…The function of p53 is critical in both reprogramming and malignant cell transformation to control the spread of damaged cells. The p53-dependent counter selection of DNA-damaged cells during reprogramming has been demonstrated by increased DNA damage foci and increased phosphorylation of the serine/threonine kinase ataxia telangiectasia mutated (ATM), [16][17][18][19][20] a well-known primary regulator of the cellular response to DNA double-strand breaks that has begun to emerge as a central DNA damage checkpoint that connects cancer predisposition with cellular bioenergetics; 94,95 thus, it has been suggested that the DNA damage response (DDR) activated during the induction of pluripotency might be equivalent to the oncogene-induced DDR that occurs during OIS, 2,17 when the cell proliferation and transformation induced during oncogene activation in early tumorigenesis is restrained by cellular senescence. The DDR that is mounted upon expression of the Yamanaka reprogramming factors is not only compatible with OSKM/OSK-driven DNA replicationinduced DNA damage, but also with the generation of reactive oxygen species (ROS), which may explain why reprogramming is significantly more efficient under low oxygen conditions or in the presence of antioxidants, such as vitamin C. 96,97 We have recently reported that metformin treatment, through the promotion of enhanced mitochondrial biogenesis and oxidative stress, may lower the threshold for cellular senescence by activating an ATM-dependent pseudo-DDR, which occurs regardless of the p53 status.…”
Section: Discussionmentioning
confidence: 99%
“…The function of p53 is critical in both reprogramming and malignant cell transformation to control the spread of damaged cells. The p53-dependent counter selection of DNA-damaged cells during reprogramming has been demonstrated by increased DNA damage foci and increased phosphorylation of the serine/threonine kinase ataxia telangiectasia mutated (ATM), [16][17][18][19][20] a well-known primary regulator of the cellular response to DNA double-strand breaks that has begun to emerge as a central DNA damage checkpoint that connects cancer predisposition with cellular bioenergetics; 94,95 thus, it has been suggested that the DNA damage response (DDR) activated during the induction of pluripotency might be equivalent to the oncogene-induced DDR that occurs during OIS, 2,17 when the cell proliferation and transformation induced during oncogene activation in early tumorigenesis is restrained by cellular senescence. The DDR that is mounted upon expression of the Yamanaka reprogramming factors is not only compatible with OSKM/OSK-driven DNA replicationinduced DNA damage, but also with the generation of reactive oxygen species (ROS), which may explain why reprogramming is significantly more efficient under low oxygen conditions or in the presence of antioxidants, such as vitamin C. 96,97 We have recently reported that metformin treatment, through the promotion of enhanced mitochondrial biogenesis and oxidative stress, may lower the threshold for cellular senescence by activating an ATM-dependent pseudo-DDR, which occurs regardless of the p53 status.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ATM-deficient lymphoblastoid cells exhibit an intrinsic upregulation of ROS and mitochondrial dysfunction [32]. Using transcriptomics, proteomics and metabolomics, Cheema et al have reported that ATM regulates purine, pyrimidine and urea cycle pathways, by way of its control of oxidative stress and activation of AMPK [33]. As noted above, other recent studies have shown that AMPK phosphorylation by IGF-1 and AICAR is ATM-dependent activity [21; 22].…”
Section: Discussionmentioning
confidence: 99%
“…Although we should acknowledge that directional interactions between ATM and AMPK could be context-specific (i.e., some reports have implicated ATM as a downstream effector of AMPK, whereas other studies have provided evidence that ATM acts upstream of AMPK to mediate the therapeutic effects of metformin), [101][102][103][104][105] metformin's ability to acts as a general activator of the ATM/AMPK axis and, therefore, of both the ATM-driven DDR pathway and the ATM-driven cellular redox signaling, should play a pivotal role at initiating the surveillance senescence mechanism in HDFs.…”
Section: 101mentioning
confidence: 99%